2009
DOI: 10.1007/s00425-009-1080-6
|View full text |Cite
|
Sign up to set email alerts
|

A tomato enzyme synthesizes (+)-7-iso-jasmonoyl-l-isoleucine in wounded leaves

Abstract: Jasmonoyl-L-isoleucine (JA-Ile) is a key jasmonate signal that probably functions in all plant species. The JASMONATE RESISTANT 1 (JAR1) enzyme synthesizes JA-Ile in Arabidopsis [Arabidopsis thaliana (L.) Heynh.], but a similar enzyme from tomato [Solanum lycopersicum (L.)] was not previously described. Tomato SlJAR1 has 66% sequence identity with Arabidopsis JAR1 and the SlJAR1-GST fusion protein purified from Escherichia coli catalyzed the formation of JA-amino acid conjugates in vitro. Kinetic analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 47 publications
(88 reference statements)
5
54
0
Order By: Relevance
“…Further experiments, including study of JMT expression in mechanically wounded tissues of Hippeastrum, should shed more light on the role of jasmonates during processes leading to achievement of immunity. Recent studies revealed that jasmonoyl-L-isoleucine (JA-Ile) acts as a key jasmonate signal (Suza and Staswick, 2008;Suza et al, 2010), so the role of JA-Ile in the response to wounding in Hippeastrum bulb scales also presents an area for investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Further experiments, including study of JMT expression in mechanically wounded tissues of Hippeastrum, should shed more light on the role of jasmonates during processes leading to achievement of immunity. Recent studies revealed that jasmonoyl-L-isoleucine (JA-Ile) acts as a key jasmonate signal (Suza and Staswick, 2008;Suza et al, 2010), so the role of JA-Ile in the response to wounding in Hippeastrum bulb scales also presents an area for investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, JA-levels correlate tightly with levels of JA-Ile even the former compound accumulates up to ten-fold higher levels in A. thaliana, tomato or tobacco. 9,10,11 Surprisingly, the highest biological activity in terms of JA-responses was observed with coronatine ( Fig. 1), a phytotoxine which does not occur in plants, but is formed by several strains of Pseudomonas syringae.…”
Section: Chemistry and Metabolites Of Jamentioning
confidence: 99%
“…32 Recently quantitative analysis of (+)-7-iso-JA-Ile the terminal ligand of the JA receptor was shown. 11 Here the derivatization with PFBB performed in the known procedure was done only for 15 min. Consequently, epimerization of isomers could be strongly reduced, and there was no epimerization of (-)-JA-Ile to (+)-7-iso-JA-Ile and most of the JA-Ile of wounded tomato leaves could be stably detected as (+)-7-iso-JA-Ile for several hours.…”
Section: (+)-7-iso-jasmonoyl-l-isoleucine Can Be Quantified As Stablementioning
confidence: 99%
See 1 more Smart Citation
“…39,40 The synthesized JA consists of two pairs of enantiomers, (-)-JA and (+)-JA, as well as (+)-7-iso-JA and (-)-7-iso-JA, each of which could not be separated on C18 column due to chiral centers of C-3 and C-7 shown in Fig. S3 (Supporting Information).…”
Section: Epimerization Separation Of Endogenous (-)-Jamentioning
confidence: 99%